Особливості розвитку молодіжної участі у волонтерській діяльності - Корпач, Надія Іванівна; Олешак, Світлана Петрівна; Korpach, Nadiia I.; Oleshak, Svitlana P. (Національна академія педагогічних наук України, Інститут проблем виховання, 2014)
У статті розкрито значення молодіжної участі в усіх сферах життєдіяльності суспільства, розглянуто поняття «участь» та її рівні.Автором доведено, що волонтерська діяльність є складовою молодіжної участі. За результатами дослідження сучасного стану молодіжної участі у волонтерської діяльності рекомендовано більше уваги приділяти розробленню та реалізації різноманітних проектів.Lesia Ukrainka Eastern European National University (Lutsk, Ukraine). The article reveals the importance of youth participation in all spheres of society, defines the concept «participation» and its level. The authors have shown that volunteering is a part of youth participation, youth activities as volunteer groups, regardless of the type of organization in which they operate. Volunteering is present in awareness raising, prevention, rehabilitation, recreational, social advertising, social, security protection and fundraising areas. Popular is also such directions: health, preservation of historical and cultural heritage and the environment. The participation of young people in volunteer movement allows them through charitable activities make a personal contribution to solving social problems, selfrealization, by initiating projects and programs that are socially useful. To encourage youth participation in volunteer activities, it is recommended to focus more on writing and implementation of various projects.
Features of the Development of Youth Participation in Volunteer Activities
Keywords: участь; молодіжна участь; волонтерська діяльність; розвиток молодіжної участі; participation; youth involvement; volunteer activities; developmentof youth participation